Inferring palaeoecology in extinct tremarctine bears (Carnivora, Ursidae) using geometric morphometrics - Figueirido, Borja (2009)
In this study we explore the ecomorphological patterns of extinct tremarctine bears in South America during the Great American Biotic Interchange (GABI). These patterns are used to derive palaeoautoecological inferences in extinct tremarctines and their palaeosinecological relationships within Plio-Pleistocene ecosystems. We used geometric morphometrics of landmark data to recover the shape of the craniomandibular skeleton of bears. The results reveal different ecomorphological specializations in extinct tremarctines during the Plio-Pleistocene of South America. Indeed, these bears could have increased the percentage of plant matter in their diets according with the increased diversity of large carnivores in South America after the GABI. Omnivorous bears retain the ability to behave as carnivores or herbivores depending on resource availability. This fact strongly supports that bears are one of the most ecologically and morphologically adaptable members of the large carnivore guild. Moreover, their skull morphology could reflect ecological adaptations under different selection pressures with the required evolutionary time